Situation Report: Yugoslavia, 30 November 1984 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Reform of Yugoslav Party under Discussion / by Slobodan Stankovic The Serbian CP's Appeal for Reform / by Zdenko Antic Diversity of Views on Reform and Recovery / by Slobodan Stankovic Trial of Six Dissidents Begins in Belgrade / by Slobodan Stankovic The Belgrade Trial Continues and Adjourns / by Slobodan Stankovic Vladimir Dedijer Discusses Human Rights Violations in Yugoslavia / by Zdenko Antic Yugoslavia's Spanish Civil War Veterans Call for Action / by Zdenko Antic Trade Unions Reluctantly Approve Strikes / by Slobodan Stankovic Official Yugoslavia Mourns Indira Gandhi as a Great Nonaligned Leader / by Zdenko Antic Patriarch Pimen of Russia Visits Yugoslavia / by Zdenko Antic Anti-Moslem Feelings Denied / by Slobodan Stankovic Belgrade's Criticism of "Monolithic Unity"; Stalin's Crimes Recalled / by Slobodan Stankovic